Sepsis of Patients Infected by SARS-CoV-2: Real-World Experience From the International HOPE-COVID-19-Registry and Validation of HOPE Sepsis Score - Abumayyaleh, Mohammad; Nuñez-Gil, Iván J.; El-Battrawy, Ibrahim; Estrada, Vicente; Becerra-Muñoz, Víctor Manuel; Uribarri, Aitor; Fernández-Rozas, Inmaculada; Feltes, Gisela; Arroyo-Espliguero, Ramón; Trabattoni, Daniela; López Pais, Javier; Pepe, Martino; et al. (Frontiers in Medicine, 2021)
Background Sepsis patients with a concomitant Coronavirus (COVID-19) infection are related to a high morbidity and mortality rate. We investigated a large cohort of sepsis patients with a concomitant COVID-19 and we developed a risk score for the estimation of sepsis risk in COVID-19. Methods We conducted a sub-analysis from the international Health Outcome Predictive Evaluation Registry for COVID-19 (HOPE-COVID-19-Registry). Out of 5,837 patients with COVID-19, 624 patients were diagnosed with sepsis according to the Sepsis-3 International Consensus. Results In multivariable analysis, the following risk factors were identified as independent predictors for developing sepsis: current smoking, tachypnoea (>22 breath per minute), haemoptysis, peripheral oxygen saturation (SpO2) < 92%, blood pressure (BP) (systolic BP< 90mmHg and diastolic BP <60mmHg), Glasgow coma scale (GCS) <15, elevated procalcitonin (PCT), elevated troponin I (TnI), and elevated Creatinine > 1.5 mg/dl. By assigning odds ratio weighted points to these variables, the following three risk categories were defined to develop sepsis during admission: low-risk group (probability of sepsis 3.1-11.8%); intermediate-risk group (24.8-53.8%); high-risk-group (58.3-100%). A score of 1 was assigned to current smoking, tachypnoea, decreased SpO2, decreased blood pressure, decreased GCS, elevated PCT, TnI, and creatinine, whereas a score of 2 was assigned to haemoptysis. Conclusions The HOPE Sepsis Score including 9 parameters is useful in identifying high-risk COVID-19 patients to develop sepsis. Sepsis in COVID-19 is associated with a high mortality rate.